RANCANG BANGUN SISTEM E-VOTING BERBASIS WEB - Charlene Alicia Wagiu; Yulianus Palopak (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2017)
The election process becomes very important in determining the desired outcome for the voters. The election process is often hampered by a variety of issues, such as the process of gathering and recounting the result sometimes takes time. For that we need a system that can facilitate the selection process so that it can provide quick and accurate results. The purpose of this study is to build a system that can provide convenience for students of the Faculty of Information Technology UNAI in running the democratic process to select the Chairman of the Student Association. The system is designed web-based so it will be easier in the process of taking voting, vote counting and announcement of the selected winners. The method used in building this system is using SDLC method with Waterfall model which consists of stages of Analysis, Design, Implementation and Maintenance. The results of the design of this system can be used in selecting the pair chairman and vice chairman of Student Association Faculty of Information Technology UNAI. The election process can run more orderly, regularly and faster especially in vote counting and winner announcement because it is done through the system. It is expected that in the future this system can be developed and applied to other election process and can be made on other platforms.